PENGARUH MODEL DAN SIFAT MATERIAL PADA ANALISIS METODE ELEMEN HINGGA BALOK TABUNG BAJA BUNDAR DIIISI BETON - Effendi, Mahmud Kori (Semarang State University, 2017)
The composite material concrete filled steel tubes, CFST) begin widely recommended in modern structural projects. This material is made of steel tubes filled with concrete. This CFST structure has better ductility than the conventional structure. The three-dimensional finite element modelby means of MSC Marc Mentat software is done by using non-linear material properties for both the steel and concrete. The non-linear geometry is also considered. The results of the finite element analysis method are then compared with experimental results of circular steel tubes filled with concrete. The results of this analysis for both load-deflection and collapse conditions are quite agree with the experimental results. However, the buckling phenomena cannot be modeled in the analysis of the finite element method. The effect of finite element model, which is half span and a quarter of half span, is investigated. The results of this analysis are similar to the results of full-scale analysis. There is plastic hinge in the middle of the beam span. The influence of the material properties of linear and non-linear geometric properties are also investigated. The the plastic hinge did not occur in the middle of beam span.